EXPLORING THE CORRELATION BETWEEN STUDENTS’ READING COMPREHENSION OF REFERENCE BOOKS AND THEIR ORAL PRESENTATION SKILLS IN LEARNING MATERIALS THROUGH YOUTUBE - Muhammad Andriana Gaffar; Paulina Novarita; Revalda Ratulisa; Rina Puspitasari (University of Kuningan, 2025)
This study investigates the correlation between students’ reference book reading comprehension and their oral presentation skills when delivering educational content through YouTube. Despite extensive research on language skills development, the specific relationship between academic reading comprehension and digital presentation capabilities remains underexplored. Using an explanatory correlational design, this study assessed 7th-semester English Education students at Universitas Islam Nusantara through reading comprehension tests, YouTube presentation evaluations, and perception questionaires. Result revealed a strong positive correlation (r = 0.712, p = 0.009) between reference book comprehension and presentations effectiveness, particularly in content structure, clarity, and delivery confidence. Regression analysis demonstrated that reading comprehension activities significantly predicts oral presentations performance, suggesting that integrated pedagogical approaches combining reading comprehension activities with digital presentation practice could enhance students’ communication competencies. These findings contribute to our understanding of digital literacy development in language education and highlight the potential of YouTube as a platform for self-assessment and skills enhancement.